Tari Tunjung Biru - Pertiwi, Ni Wayan Eka Sri; Arshiniwati, Ni Made; Gunarta, I Wayan Adi (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
Tunjung Biru is a dance creation that originating from Sang Hyang Dedari in Br. Pujung Kaja, Sebatu, Tegallalang, Gianyar. Tunjung Biru has a beautiful appearance with strong characteristics, creatively expressed in the New Creation Dance with a magical religious theme. The purpose of creating Tunjung Biru is to preserve and also introduce the art in Br. Pujung Kaja, Sebatu, Tegallalang, Gianyar, especially Sang Hyang Dedari. The creation of this dance creation utilizes the angripta-sasolahan method by I Kt. Suteja, involving stages: planning (ngarencana), ritual ceremony (nuasen), selection and improvisation (makalin), formation (nelesin), and first performance (ngebah). Ngerencana involves observation, thinking, and imagination about the creative sources used. Nuasen is a ritual ceremony before improvising movements, including a prayer performed by all dancers. Makalin involves selecting supporting elements and improvising movements. Nelesin is the formation stage, summarizing the obtained improvisations. Ngebah is the first performance to reveal the work and receive feedback. The creation process incorporates the theories of imagination, symbols, and aesthetics. Tunjung Biru is presented as a New Creation Dance performed by 7 female dancers with kekereb properties, minimalistic makeup, and attire inspired by Sang Hyang Dedari in black and white tones. Accompanied by Gamelan Selonding to enhance the atmosphere of each presented structure. The novelty in this work can be seen from the costumes used, the music, to the new movement patterns to get the characteristic movements such as the Nyapuh Movement, the Dedari Tunjung Biru Movement, and the Tenget Movement so that this work becomes beautiful, supported by chanting hymns and lighting which helps the artist to create convey the desired atmosphere.